Water and wastewater engineering : water supply and wastewater removal - Shammas, Nazih K.; Wang, Lawrence K. (Wiley, 2011)
"This book series of Water and Wastewater Engineering have been written in a time of mounting urbanization and industrialization and resulting stress on water and wastewater systems. Clean and ample sources of water for municipal uses are becoming harder to find and more expensive to develop. The book is comprehensive and covers all aspects of water supply, water sources, water distribution, sanitary sewerage and urban stormwater drainage. This wide coverage is helpful to engineers in their every day practice."-- Provided by publisher